AN ANNOTATED TRANSLATION OF “MY POINT... AND I DO HAVE ONE” BY ELLEN DEGENERES - Nitisari, Dwi (Journal of Language and Literature, 2014)
This is an annotated translation research. The problems of this research are (1) What are the problems encountered by the translator/ researcher during the process of translation; (2) What are the plausible solutions to the problems encountered by the translator/ researcher during the process of translation. The purposes of this research are (1) To attain factual information concerning the problems encountered by the translator/ researcher during the process of translating the source text into the target text, namely from English into Indonesian; (2) To present plausible solutions to the problem encountered by the translator/ researcher during the process of translation. The methods of this research are the introspective and retrospective method. The result of the analysis revealed that not all items of the principles of translation and not all of those strategies of translation were used for analysis. From the six items in the principle of translation, there are five principles of translation namely Meaning (5 data), Source Language Influence (2 data), Style and Clarity (5 data) Idiom (5 data) and register (3 data).  Of  each  strategies, namely syntactic strategies there are cohesion change (1 data), unit shift (2 data), loan (3 data), calque (2 data), and phrase structure change (1 data), of semantic strategies namely paraphrase (4 data), and of pragmatic strategies namely cultural filtering (2 data), Synonomy (1 data), and interpersonal change (4 data). The finding in this research revealed that an idiom in the target text is not used to translate an idiom in the source text. The idioms in this study are translated as non idiom in this research. Other finding is that there is no active target text which derived from passive source text what exist in the other way round. Another findings shows that the word I is translated into aku. I refers to the author in line with the conversation with herself in the context and when the author in line with the conversation with the reader in the context, the word I is translated into saya.The implications of this research are 1) The researcher/ translator should master the English language as well as the Indonesian language; 2) The researcher/ translator should master the theories of translation including the principle of translation and translation strategies as well as the theories of both languages; 3) The researcher/ translator should be competence in using application program, especially Microsoft Office; 4) Translator has no friends except dictionaries.  Key Words: Annotated, Translation, introspective, retrospective